A high refractive index resist for UV-nanoimprint soft lithography based on titanium-containing elemental polymer oligomers. Issue 1 (7th December 2021) - Qiu, Junlun; Hu, Getian; Wang, Yuqiao; Wang, Yurui; Luo, Ming; Hu, Xin
Abstract : A UV-curable high refractive index resist ( n D = 1.7063) for UV-nanoimprint lithography is synthesized and the refractive index can be further improved to 1.7327 after baking. 50 nm resolution patterns are faithfully imprinted into the resist film. Abstract : This paper demonstrates a novel resist with a high refractive index for UV-curing nanoimprint lithography based on an o -phenoxyphenyl acrylated polytitanoxane oligomer. The oligomer is synthesized by hydrolysis and condensation of Ti-OEt and the o -phenoxyphenyl groups are grafted onto the backbone via the reaction between o -phenylphenoxyethyl acrylate (OPPEA) and titanium(iv ) ethoxide. Acrylate groups are introduced by the chelate reaction between titanium(iv ) ethoxide and 2-(methacryloyloxy)ethyl acetoacetate (MAEAA). The chelate rings and benzyl rings greatly improve the resin stability: the resin retains solubility in organic solvents even when it is stored in an air atmosphere for at least 48 hours at room temperature. The resist has an excellent UV transmittance (80% at 365 nm), a high modulus (1.97 GPa) and a high refractive index (1.7063 at 589.3 nm), and the refractive index can be further improved to 1.7327 after baking. A UV-nanoimprint protocol is also optimized and high-resolution patterns with 50 nm line width are faithfully imprinted into the resist film. Furthermore, the resin patterns can be used as a mask for duplicating more PDMS molds, which greatly reduces the risk of master damage.